Mechanization and agricultural supply response in the Sahel : a farm-level profit function analysis - Savadogo, Kimseyinga; Reardon, Thomas; Pietola, Kyösti (University of Ouagadougou, Ouagadougou, Burkina Faso, 1995)
This paper uses a profit function approach with farm-level survey data from Burkina Faso to estimate the supply responsiveness of farm households to changes in prices and non-price factors, for individual crops and aggregate output. The sample is stratified first by agro-ecological zone and then, with an endogenous partition, into animal traction and manual (hand-tool) households. Three main conclusions emerge. First, the results run counter to the common pessimism regarding Sahel agriculture's ability to respond to better incentives (such as those created by the recent devaluation of the CFA franc) particularly for cash cropping. Second, aggregate output responds positively to increases in the price of currently commercialized crops (cotton and maize) among traction households in the zone with the most favourable agro-climate, the Guinean zone thus averting the fear that price increases only lead to crop mix shifts. Third, absolute levels of response for cash crops and for aggregate output are much higher where non-price factors are propitious specifically, in the favourable agro-climate and among animal traction households that use fertilizer. Supply response is more limited in less favourable agro-climates and among households limited to hand-tool technologies. The results underscore the greater flexibility of the animal traction farmers to respond to economic incentives for cotton and maize. Donor and government programmes that promote animal traction and fertilizer adoption can via agrarian capital formation reduce structural constraints to farmer response to macro incentives.
Keywords: Ma; Länsi-Afrikka; Afrikka; maatilat; maatalousyritykset; koneellistaminen; puhdas tuotto; tarjonta; kannattavuus; ekonometria; farms; mechanization; profit; supply; profitability; econometrics; Western Africa